A revisionary approach of Colombian Ananteris (Scorpiones, Buthidae): two new species, a new synonymy, and notes on the value of trichobothria and hemispermatophore for the taxonomy of the group - Botero-Trujillo, Ricardo; D, Eduardo Flórez (Zootaxa, 2011)
Some contributions to the knowledge of the buthid scorpion genus Ananteris Thorell, 1891 in Colombia are herein presented, based upon the examination of over 100 specimens. Ananteris ochoai sp. nov. and Ananteris solimariae sp. nov. are described from Nariño and Santander departments, respectively. The recently described Ananteris hasshy Teruel & Roncallo, 2008 is synonymized under Ananteris columbiana Lourenço, 1991 based on several evidences from morphology. The males of Ananteris dorae Botero-Trujillo, 2008, Ananteris ehrlichi Lourenço, 1994 and Ananteris myriamae Botero-Trujillo, 2007, and the female of Ananteris arcadioi Botero-Trujillo, 2008 are described for the first time. Ananteris meridana González-Sponga, 2006 is reported for the first time for Colombia and the genus Ananteris for the departments of Cundinamarca, Santander and Norte de Santander. Likewise, new locality records are given for A. arcadioi, A. dorae and A. myriamae. Revised diagnoses and data on intraspecific variability are provided for A. arcadioi, A. columbiana, A. dorae, A. ehrlichi, A. meridana and A. myriamae. Hemispermatophore morphology is described for the first time for A. arcadioi, A. columbiana, A. dorae, A. ehrlichi, A. meridana, A. myriamae, A. ochoai sp. nov. and A. solimariae sp. nov., providing evidence of this structure’s taxonomic usefulness and revealing a paramount need to describe it in further taxonomic works on Ananteris. Some notes on the use of the fixed finger trichobothria for the definition of Ananteris speciesare provided. A distribution map plotting the known locality records of the thirteen Colombian species of Ananteris and a key to their identification are also included. Finally, the name ‘Ananteris antioquensis’, used by Otero et al. (2004) but never published, is herein deemed a nomen nudum.